Application of arc plasma for a deposition of superconducting films - Langner, J.; Russo, R.; Catani, L.; Tazzari, S.; Cirillo, M.; Czaus, K.; Merlo, V.; Tazzioli, F.; Proch, D.; Koval, N.N.; Lopatin, I.V. (Вопросы атомной науки и техники, 2002)
This work was supported mainly by Italian INFN grant ARCO and DESY. The authors are grateful to Dr. S.Calatroni and Dr. C.Benvenuti of CERN for constant support of cathodes and samples substrates. We would like to thank Prof. M.Sadowski for help in the arrangement of the new laboratory in Swierk and very useful disscusion. We are indebted to the group of Prof. Vaglio (University of Naples) for help and support forinductive measurements). We are also very indebted to R.Sorchetti and G.Fuga from INFN, LNF Frascati and A.Trembicki as well as ing.R. Mirowski from IPJ Swierk for the constant help during the design, construction and commissioning of our apparatus.